CHARACTERISTICS OF RICE SOILS FROM THE TIDAL FLAT AREAS OF MUSI BANYUASIN, SOUTH SUMATRA - Prasetyo, B.H.; Suping, S.; H., Subagyo; ., Mujiono; Suhardjo, H. (Indonesian Agency for Agricultural Research and Development - MOA, 2001)
Tidal flats in the Musi Banyuasin region that cover more than 200,000 ha are the largest area for agricultural development in South Sumatra Province. Only about a half of this has been used for tidal swamp rice fields, therefore, the other half needs to be developed. To obtain a better understanding of their properties for appropriate soil management, soil characteristics of the area need to be studied. To characterize the soil,thirty-four soil samples from seven soil profiles were analyzed for their chemical and mineralogical composition at the laboratories of the Center for Soil and Agroclimate Research and Development. The results indicate that soils from the tidal flat areas have an aquic soil moisture regime, the upper parts of the soils are mostly ripe, and most of the pedons show thepresence of sulfidic materials below 65 cm of the mineral soil surface. The soils are classified as Sulfic Endoaquept (P1, P2), Histic Sulfaquent (P3), Typic Sulfaquept (P4), Fluvaquentic Endoaquept (P5), and Sulfic Hydraquent (P6, P7). Mineral composition of the sand fraction is dominated by quartz, while the clay minerals consist of predominantly kaolinite, mixed with small amount of smectite, illite, quartz, and crystoballite. Organic carbon content is high to very high, potentialphosphate content of most pedons ranges from very low to medium, while potential potassium content varies from very low to medium in the upper layers and medium to very high in the bottom layers. Phosphate retention of topsoil sample varies from 56 to 97%, and is positively correlated (r2 = 0.73) with aluminum from amorphous materials. Exchangeable cations are dominated by Mg cation, and in all pedons cation exchange capacity values are medium to very high, and seem to be influenced by organic carbon. Specific chemical properties, particularly soil pH and content of exchangeable aluminum exhibit a significant change about 1-2 months after soil samples were taken from the field. Theoretically, interactionbetween good water management and fertilizer application are among the choices of management to make these soils productive.